Seedbed Preparation Techniques and Weed Control Strategies for Strip‐Planting Rhizoma Peanut into Warm‐Season Grass Pastures. Issue 4 (1st July 2014) - Castillo, Miguel; Sollenberger, Lynn; Blount, Ann; Ferrell, Jason; Na, Chae‐In; Williams, Mary; Mackowiak, Cheryl
ABSTRACT: Planting rhizoma peanut ( Arachis glabrata Benth.; RP) in strips into bahiagrass ( Paspalum notatum Flüggé) pastures can reduce establishment cost relative to conventional techniques, but research is needed to determine the best seedbed preparation methods. The objectives were to quantify the effects of four seedbed preparation techniques: glyphosate + tillage, tillage only, glyphosate + no‐till, and sod removal; and four postemergence weed control strategies: control (no herbicides, no mowing), mowing (every 28 d to 10‐cm stubble height), imazapic (0.29 L ha –1 ), and imazapic + 2, 4‐D amine (0.29 and 0.58 L ha –1, respectively). Sprout emergence ranged from 90 to 119 m 2 in treatments where tillage occurred compared with 54 to 58 m –2 in no‐till and sod removal. Nevertheless, by season end RP canopy cover and frequency of occurrence favored no‐till (21% cover and 70% frequency) compared with the other treatments (≤14% cover and 53% frequency). Weed control strategy after planting had a greater effect on establishment success than seedbed preparation. By season end, RP cover and frequency were greater for imazapic (25 and 64%, respectively) and imazapic + 2, 4‐D (23 and 64%, respectively) than for the control (10 and 42%, respectively) and mowing treatments (7 and 36%, respectively). Glyphosate followed by no‐till planting and postemergence use of imazapic with or without 2, 4‐D is a viable option for reduced‐cost establishment of RP in strips into bahiagrass pastures.